Güvenlikleştirme teorisi açısından İsrail'in Türk dünyası politikası - Yesevi, Çağla Gül (My University, 2017)
Çalışma kapsamında, Kopenhag Okulu teorisyenlerinin üzerinde çalıştıkları güvenlikleştirme teorisi açıklanmıştır. Bu teorinin ışığında, İsrail’in Türk Dünyası ilişkileri analiz edilmiştir. Azerbaycan, Kazakistan, Özbekistan, Türkmenistan, Kırgızistan ve Tacikistan’ın İsrail’le ilişkilerinin farklı güvenlik boyutları değerlendirilmiştir.

The securitization theory that the Copenhagen School theorists are working on is explained within the scope of the study. Israeli relations of the Turkic World have been analyzed by the vision of this theory. The different security dimensions of Azerbaijan, Kazakhstan, Uzbekistan, Turkmenistan, Kyrgyzstan and Tajikistan’s relations with Israel have been evaluated
The Turkic World Politics Of Israel From The Vision Of Securitization Theory
Keywords: Kopenhag Okulu; Güvenlikleştirme Teorisi; İsrail; Türk Cumhuriyetleri; Copenhagen School; Securitization Theory; Israel; Turkic Republics